Harmony on the hilltop through place-based socioeconomic development - Nonog, Alphonsus Rouis B.; Alex Ray P. Evangelista (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
As Baguio City continues to face rapid urbanization, public open spaces such as the Baguio City Public Market will need to be redeveloped to support sustained socioeconomic development in the foreseeable future. Aimed to redesign the market as a pluralistic, inclusive space that ensures socio economic development and community vitality among its residents, the project focuses on the people of Baguio and the market itself, while considering the broader urban design context of this market. This factors towards further understanding the local character of both the city and its people in relation to the local economy, contributing to the appropriate design approaches of architectural pluralism and place-based economic development. Although interviews with key market personnel and public market consultants reveal that providing a well-functioning, dedicated space for a public market is essential, the additional challenges of maintaining sustained interactions among the people, whether buyers or sellers or even resident or tourists, aside from the products sold is also tantamount to a successful public market design. Drawing on Baguio's identity as a melting pot of the Cordillera region, its American colonial history, status as a UNESCO Creative City, and smart city ambitions, the redesign adopts Panagbenga flowers as a central concept - a symbol for the resilience of a city abundant in resources, labor, and talent. This concept embodies a similar image, presenting how this sense of community vitality is shown throughout the city's public commercial center using floral iconography, inclusive and accessible spaces, and dedication towards highlighting the local market spaces. Overall, the redevelopment of the Baguio City Public Market stands as a landmark for creating a market environment that enhances the city's projected resilience and vitality in the future.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Public architecture -- Baguio City; Markets -- Baguio City; Markets -- Social aspects -- Baguio City; Markets -- Economic aspects -- Baguio City; Open spaces -- Baguio City; Community development -- Social aspects -- Baguio City; Community development -- Economic aspects -- Baguio City